2001
DOI: 10.1002/ajpa.10019
|View full text |Cite
|
Sign up to set email alerts
|

Origin of human bipedalism: The knuckle-walking hypothesis revisited

Abstract: Some of the most long-standing questions in paleoanthropology concern how and why human bipedalism evolved. Over the last century, many hypotheses have been offered on the mode of locomotion from which bipedalism originated. Candidate ancestral adaptations include monkey-like arboreal or terrestrial quadrupedalism, gibbon-or orangutan-like (or other forms of) climbing and suspension, and knuckle-walking. This paper reviews the history of these hypotheses, outlines their predictions, and assesses them in light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
164
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(174 citation statements)
references
References 162 publications
2
164
0
Order By: Relevance
“…Further discoveries of earlier bipedal hominins dating back to at least approximately 6 Ma [65] only increased the gap between bipedalism and stone tools [8]. Thus, tool-related behaviours have generally no longer been thought to have a cause-effect relationship with the origin of hominin bipedalism [50,117,118]. However, it may be worthwhile to revisit Darwin's original hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Further discoveries of earlier bipedal hominins dating back to at least approximately 6 Ma [65] only increased the gap between bipedalism and stone tools [8]. Thus, tool-related behaviours have generally no longer been thought to have a cause-effect relationship with the origin of hominin bipedalism [50,117,118]. However, it may be worthwhile to revisit Darwin's original hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…This way of walking is distinct from the knuckle walking of the great apes, who bear their weight on the dorsal surface of their middle phalanges. 13 Knuckle walking has been regarded as the ancestral method of locomotion based on the anatomy of wrist and phalangeal bones. 14 The phenotype described here demonstrates that a single gene defect can result in efficient palmigrade walking in humans in spite of a wrist that is generally thought to be anatomically not adapted to this form of locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…This "vertical climbing hypothesis" has been widely accepted (but see Gebo, 1996;Richmond and Strait, 2000;Richmond et al, 2001). Biomechanical considerations suggested that, during vertical climbing, the stresses and muscle activities in the hindlimbs are very similar to those during bipedal walking (Fleagle et al, 1981;Prost, 1980).…”
mentioning
confidence: 94%
“…At present, more research on hominoid locomotion and a functional linking with morphological features are clearly warranted (Richmond et al, 2001). A comparative approach should include as many primate species and locomotor types as possible, because the extant apes and humans are all highly specialized in terms of locomotion and have diverged from the primitive condition of their last common ancestor.…”
mentioning
confidence: 99%